A colorimetric indicator based on copper nanoparticles for volatile sulfur compounds to monitor fish spoilage in intelligent packaging. (September 2022) - Teymouri, Zahra; Shekarchizadeh, Hajar
Abstract: A colorimetric indicator based on copper nanoparticles (CuNPs) was developed to detect volatile sulfur compounds during fish spoilage. The colorimetric indicator based on CuNPs showed excellent selectivity toward sulfur compounds against other volatile components produced during fish spoilage. The prepared indicator had a sensitive and irreversible response due to the strong binding of Cu with sulfur compounds. The very low limit of detection (1.53 µg/mL) and limit of quantification (4.63 µg/mL) of the colorimetric indicator based on CuNPs showed high indicator sensitivity. The indicator response was not affected by the moisture, pH, and time. Fish quality characteristics such as total viable count (TVC), pH, and total volatile basic nitrogen (TVB-N) were determined to analyze the efficiency of the indicator in the timely investigation of fish quality during storage. The visible color changes of the indicator had a good correlation with the fish quality. pH, TVB-N, and TVC of the fish samples were 6.5, 15.5 (mg/100 g), and 7.4 Log (CFU/g), respectively. The orange-cream color of the indicator with a ΔE of 8.67 showed the semi-freshness of fish after three days of storage in the refrigerator. White, yellow, and brown colors of the colorimetric indicator based on CuNPs were related to fresh, semi-fresh, and spoiled fish, respectively. The prepared indicator based on CuNPs can be used as a very simple and low-cost but useful way for real-time monitoring of fish spoilage with distinct color changes visible to the naked eye in smart packaging. Highlights: A colorimetric indicator based on copper nanoparticles (CuNPs) was developed. The colorimetric indicator showed excellent selectivity toward sulfur compounds. The prepared indicator had a sensitive and irreversible response. The visible color changes of the indicator had a good correlation with the fish quality. White, yellow, and brown colors of the indicator were related to fresh, semi-fresh, and spoiled fish, respectively.